THE NARRATIVE CONSTRUCTION OF VIOLENCE IN THE PARAENSE AMAZON IN THE NON-FICTION BOOK THE MASSACRE: ELDORADO DO CARAJÁS - Cristina Silva da Costa, Alda; Dias, Erica (Brazilian journalism research, 2024)
ABSTRACT – This article aims to understand how land conflict narratives in the Amazon are constructed in literary journalism – specifically the Eldorado do Carajás massacre, one of the more serious confrontations between military police and workers, and resulted in 19 farmers shot dead and more than 50 injured, in southeastern Pará. The corpus analysis selected for this work is the 2019 non-fiction book O massacre: Eldorado do Carajás - Uma história de impunidade (in English, The Massacre: Eldorado do Carajás – A Story of Impunity) written by journalist Eric Nepomuceno. Under the lens of Motta’s (2007) “pragmatic analysis of journalistic narrative”, we understand this book, with the results showing that it is essential to pay attention to cases of violence in the countryside, the devastation of the environment, and the excessive repression of people fighting for their right to land. RESUMO – O presente artigo visa compreender como a narrativa dos conflitos por terra na Amazônia – em específico, o massacre de Eldorado do Carajás, um dos mais graves confrontos entre a polícia e os trabalhadores, que resultou em 19 trabalhadores mortos e mais de 50 feridos no sudeste paraense –, é construído no jornalismo literário. O corpus de análise selecionado é o livro-reportagem O massacre: Eldorado do Carajás – Uma história de impunidade (2019), escrito pelo jornalista Eric Nepomuceno. Sob as lentes da “análise pragmática da narrativa jornalística” de Motta (2007), tecemos a compreensão da referida obra, com a constatação, como resultados, da imprescindibilidade de atenção aos casos de violência no campo, da devastação do meio ambiente e da repressão demasiada ao povo que luta por seu direito à terra. RESUMEN – Este artículo tiene como objetivo comprender cómo se construye en el periodismo literario la narrativa de los conflictos por la tierra en la Amazonia – en concreto, la masacre de Eldorado do Carajás, uno de los enfrentamientos más graves entre la policía y los trabajadores, que se saldó con 19 trabajadores muertos y más de 50 heridos en el sureste de Pará. El corpus de análisis seleccionado es el libro-reportaje O massacre: Eldorado do Carajás - Uma história de impunidade (2019), escrito por el periodista Eric Nepomuceno. A través de la lente del “análisis pragmático de la narrativa periodística” de Motta (2007), hemos llegado a la comprensión del libro, con los resultados que muestran que es esencial prestar atención a los casos de violencia en el campo, la devastación del medio ambiente y la represión excesiva de las personas que luchan por su derecho a la tierra.